The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jad.2021.06.073
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review of the prevalence of anxiety among the general population during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic has had an adverse effect on the mental health of population worldwide. This study was conducted to systematically review the existing literature to identify the individuals at higher risk of anxiety with a view to provide targeted mental health services during this outbreak. Methods In this study, the studies focusing on anxiety prevalence among the general population during the COVID-19 pandemic were searched in the PubMed, EMBASE, Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 35 publications
1
41
3
Order By: Relevance
“…Because of the alarming effects of the pandemic and lockdown on mental health and suicide (Bueno-Notivol et al, 2020;Dubé et al, 2021;Kan et al, 2021;Xiong et al, 2020), the current study underlines the protective role of tolerance for mental pain in reducing psychological distress and suicidal ideation during the pandemic. Evidence-based public health interventions focused on tolerance for mental pain during a pandemic are needed in order to effectively reduce suicide risk and promote resilience among the general population worldwide.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Because of the alarming effects of the pandemic and lockdown on mental health and suicide (Bueno-Notivol et al, 2020;Dubé et al, 2021;Kan et al, 2021;Xiong et al, 2020), the current study underlines the protective role of tolerance for mental pain in reducing psychological distress and suicidal ideation during the pandemic. Evidence-based public health interventions focused on tolerance for mental pain during a pandemic are needed in order to effectively reduce suicide risk and promote resilience among the general population worldwide.…”
Section: Discussionmentioning
confidence: 83%
“…A large body of evidence indicates that these restrictions, accompanied by the intense fear of severe illness, loneliness, financial problems, and uncertainty over the course of the pandemic, have profound adverse mental health implications (Bakioğlu et al, 2020;Besser et al, 2020;Brooks et al, 2020;Daly & Robinson, 2021;Landi et al, 2020b;Pakenham et al, 2020). Meta-analyses of community-based studies revealed a pooled prevalence of 18-33% of depressive symptoms (Bueno-Notivol et al, 2020) and 24-31% of anxiety symptoms (Kan et al, 2021) during the first months of the COVID-19 emergency. A systematic review, Xiong and colleagues (2020) further reported an increase in rates of psychological distress following the emergence of the pandemic among the general population in countries such as China, Spain, Italy, the USA, Turkey, Nepal, and Denmark (Xiong et al, 2020).…”
mentioning
confidence: 99%
“…To answer the research questions in this study, we developed a moderated mediation model to explore the impact of the COVID-19 pandemic on impulse buying and tested the relevant hypotheses through three experiments. Specifically, the COVID-19 pandemic as an external threat has caused consumers more anxiety, stress, and a reduced sense of control [ 14 , 15 ]. For this reason, they have needed a way to cope with external threats [ 16 ], such as impulse buying.…”
Section: Introductionmentioning
confidence: 99%
“…Depressive and anxiety disorders are widespread in the general population, especially during the current COVID-19 pandemic [1], and in a wide-range of patient populations [2][3][4][5]. They are also highly co-morbid with one another [6][7][8].…”
Section: Introductionmentioning
confidence: 99%